Pemberdayaan Usaha Kecil Menengah Melalui Bantuan Modal Usaha di Pondok Bambu Jakarta Timur - ilhamdi ilhamdi; Falhan Nian Akbar (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2018)
Small and Medium Enterprises (SMEs) sector proved more resilient in the face of crisis. conditions. And Small and Medium Enterprises (SMEs) have a strategic role in the national economic development. owever, SMEs are often overlooked due to limited government capacity. Therefore, SMEs need to get attention from both government and society in order to grow more competitive with other economic actors. This paper aims to describe community service activities undertaken in order to develop SMEs. The methods used in community service are entrepreneurship seminars and training, as well as business practices for MSME groups. And the results of these activities have a positive impact on SMEs self-reliance and increase family income.